Innate lymphoid cells in neuroinflammation - Kveštak, Daria; Mihalić, Andrea; Jonjić, Stipan; Brizić, Ilija (Frontiers in Cellular Neuroscience, 2024)
Innate lymphoid cells (ILCs) are largely tissue-resident cells that participate in the maintenance of tissue homeostasis and react early to inflammatory events. Mature ILCs are divided into three major groups based on the transcription factors required for their development and function. Under physiological conditions, ILCs are present within the choroid plexus and meninges while the CNS parenchyma is almost devoid of these cells. However, pathological conditions such as autoimmune neuroinflammation and viral infections of the CNS result in the infiltration of ILCs into parenchyma. In this article, we provide an overview of the involvement and function of the ILCs within the CNS during physiological conditions and in infections, autoimmune diseases, neurodegeneration, and injury.